Planning of Higher Education Information Technology Strategy Using TOGAF (A Case Study at AMN Cilacap) - Prayitno, Oktavianus Teguh (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2019)
Information technology that develops along with the rapid role of communication through the Internet makes technology and information systems have a position that is vital for the business alignment of an institution including higher education institutions. The strategic planning of this sector has a goal to develop the basis / guidelines in developing and developing information technology and systems to support organizational goals and increase increasingly competitive competitive advantage. Thus, the integration between business and information technology becomes important to support the competitiveness of institutions. The responsibility of Enterprise Architecture (EA) is to provide an accurate and fast information system based on the business demands of the institution. Appropriate standards and models are needed by higher education institutions to improve the alignment of business strategies and information technology. This study will explore the problems faced by AMN Cilacap and provide the development of information technology and systems needed to use EA using the Open Group Architecture Framework (TOGAF) methodology. TOGAF provides methods and tools to assist in the receipt, production, use and maintenance of corporate architecture.